Peran Ilmu Ashwat dalam Pemerolehan Bahasa Arab Perspektif Psikolinguistik - Muhammad Miftah Fathurrohman; Lina Marlina (Jurnal Sathar, 2026)
The acquisition of Arabic language cannot be separated from the mastery of sound and pronunciation aspects studied in ‘ilm al-ashwat (phonetics and phonology). However, many Arabic learners experience difficulties in pronouncing certain phonemes due to the influence of their first language and psychological factors. This study aims to analyze the role of ‘ilm al-ashwat in Arabic language acquisition from a psycholinguistic perspective. The research employed a descriptive qualitative approach using library research. Data were collected from books, scientific journals, academic articles, and other relevant literature, and analyzed through content analysis. The findings reveal that ‘ilm al-ashwat plays a significant role in helping learners recognize, differentiate, and produce Arabic sounds accurately. Arabic language acquisition is influenced by auditory perception, phonological memory, first-language interference, learning motivation, language environment, and instructional methods. Therefore, the integration of psycholinguistic principles into ‘ilm al-ashwat instruction is essential for improving Arabic language proficiency